2020
DOI: 10.52131/jee.2020.0102.0008
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Relationship between Economic Growth, Energy Consumption and CO2 Emissions: Evidence from ASEAN Countries

Abstract: This study tested the EKC (environment Kuznets curve) framework for selected 9 ASEAN countries of the time period of 1970-2019. The EKC framework hypothesis checked under 2 linkages, first one is to examine the relationship between energy consumption, GDP and CO2 and the other one is energy consumption, GDP square and CO2. The study examines both long and short run effect of energy consumption, GDP, square of GDP on carbon emission. Firstly, used Levin Lin Chu and Lm Pasaran panel unit root test to check the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Several studies Altinay and Karagol (2005); Atif and Siddiqi (2010); Shiu and Lam (2004) estimate unidirectional electricity demand to economic progress causality. On contrary to the above discussion, some studies such as (Adom, 2011;Akinwale, Jesuleye, & Siyanbola, 2013;Ciarreta Antuñano & Zárraga Alonso, 2007;Hye & Riaz, 2008;Ozun & Cifter, 2007) elucidates the causality running from economic progress to electricity demand, while many researchers show an insignificant relationship between consumption of electricity and energy consumption (Aktaş & Yilmaz, 2008;Ciarreta Antuñano & Zárraga Alonso, 2007;Eden & Hwang, 1984;Gillani & Sultana, 2020). In addition, the progress of a country is measured by economic growth, which indicates how much the country's productive capacity increases over time.…”
Section: Introductionmentioning
confidence: 93%
“…Several studies Altinay and Karagol (2005); Atif and Siddiqi (2010); Shiu and Lam (2004) estimate unidirectional electricity demand to economic progress causality. On contrary to the above discussion, some studies such as (Adom, 2011;Akinwale, Jesuleye, & Siyanbola, 2013;Ciarreta Antuñano & Zárraga Alonso, 2007;Hye & Riaz, 2008;Ozun & Cifter, 2007) elucidates the causality running from economic progress to electricity demand, while many researchers show an insignificant relationship between consumption of electricity and energy consumption (Aktaş & Yilmaz, 2008;Ciarreta Antuñano & Zárraga Alonso, 2007;Eden & Hwang, 1984;Gillani & Sultana, 2020). In addition, the progress of a country is measured by economic growth, which indicates how much the country's productive capacity increases over time.…”
Section: Introductionmentioning
confidence: 93%
“…Green awareness is accepted as difficult knowledge that required different organization resources (Zeppini & van Den Bergh, 2011), like green finance. Green finance is not only for the decline in energy consumption but also has a significant effect on economic development as well as CO2 (Gillani & Sultana, 2020;Shen et al, 2021). The term green finance defined by (Lindenberg, 2014) means "green finances to enhance the level of financial flows (from banking, micro-credit, insurance, and investment) from the public, private and not-for-profit sectors to sustainable economic development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The total degree of energy insecurity is decreased by more income and good governance (Le and Park, 2021). Gillani and Sultana (2020) have tested relationship between economic growth, energy consumption and CO 2 emissions for selected nine ASEAN countries using the EKC framework and have found the validity of the EKC in the case of those countries; that is, initially, the level of CO 2 emissions increases with the increase in economic development, and it decreases with more economic development in the later. Chontanawat (2020) has tested the same relationship in cases of Indonesia, Malaysia, the Philippines and Thailand using Granger causality and found that the first three countries support the conservative hypothesis while the last one supports the growth hypothesis.…”
Section: Literature Reviewmentioning
confidence: 99%